Effect of dye on the performance of nitrogen doped tio2 solar cell prepared via ammonia treated liquid phase depostion technique - Rahman M.Y.A.; Umar A.A.; Saad S.K.M.; Salleh M.M.; Ishaq A. (Ecole Polytechnique de Montreal, 2023)
This paper reports the utilization of nitrogen-doped TiO2 nanoparticle in dye-sensitized solar cell (DSSC). The TiO2 nanoparticles were synthesized on ITO substrate via a simple technique, namely, liquid phase deposition (LPD). 7.5% nitrogen from NH3 dopantsource was doped into the TiO2 samples by spin coating technique. The nitrogen doped TiO2 samples were then utilized as photovoltaic materials in a photoelectrochemical cell of ITO/TiO2/electrolyte/platinum sensitized with N-719, N-3 and Z-907 dyes, respectively. It was found that the photovoltaic parameters such as short-circuit current density (Jsc), open-circuit voltage (Voc), fill factor (FF) and power conversion efficiency (?) are influenced by the organic dyes. The cell sensitized with N-719 dye demonstrated the highest photovoltaic parameters. These results are supported with the UV-Vis analysis, showing that the N-719 dye possessed the broadest window absorption and the highest absorption peak in visible region of light spectrum. © 2014 J. New Mat. Electrochem. Systems.